Interventions for smoking cessation: An overview of Cochrane reviews - Chun-li Lu; Jia-xuan Li*; Qian-yun Wang*; Rui-ting Wang; Xing-ru Pan; Xiao-ying Chen; Chao-jie Wang; Rui-lin Chen; Si-hong Yang; Zhi-hui Zhao; Jing-jing Jiang; Xue-han Liu; et al. (Tobacco Induced Diseases)
Introduction Evidence of different smoking cessation interventions varies and has been assessed in many Cochrane reviews. We conducted an overview of these Cochrane reviews to summarize the effects of current interventions for smoking cessation.